REFLECTIONS REGARDING THE WITNESS'S RIGHT AGAINST SELF-INCRIMINATION - Luminița CRIȘTIU-NINU; Cătălin-Nicolae MAGDALENA (Challenges of the Knowledge Society)
Considered for a long time as the „eyes and ears of justice″, the witness has become a procedural subject around which several controversies have arisen since the entry into effect of Law no. 135/2010 on the Criminal Procedure Code. The suspected witness, the one against whom further criminal prosecution has not yet been ordered, has acquired a distinct position, shaped by the ECtHR jurisprudence and redefined by CCR dec. no. 236/2020. Although the ECtHR has repeatedly ruled that the guarantees of fairness in proceedings apply once an accusation is formulated, it has also recognized these same guarantees for individuals who are heard as witnesses, but are simultaneously suspected of committing offenses. Even after the official release of the constitutional court’s decision, there are a series of aspects that automatically, are rising debates and controversies, with the most important one being whether there is a genuine right for the witness to remain silent. Has the phrase „cannot be used against them″ in art. 118 CPP become predictable and, at the same time, a barrier against potential abuses? Can a „right to silence and non-self-incrimination″ be recognized ab initio? The balance between the general interest of a fair conduct of the criminal proceedings and the rights of the „suspected″ witness has required and continues to require practical solutions from the judicial authorities, ensuring that the right to defense and the right to a fair trial are respected.